POMPA AIR DONGKI: SOLUSI PENGADAAN AIR BERSIH UNTUK DAERAH PERBUKITAN - Andayani, Sri; Mustakim, ' (PEDULI: Jurnal Ilmiah Pengabdian Pada Masyarakat, 2017)
Dusun Brige’en Desa Paras Kecamatan Tegal Siwalan Kabupaten Probolinggo is a settlement located in a hilly area. The soil structure that is rocky causes the people difficult to dig the groundwater to fulfil their clean water needs. The flow of PDAM service cannot be used by the people because the location is far from the center of water flow. Daily, the people use the water from the water springs of Paras River that is located under Dusun Brige’en directly or binging it with water container. To solve the problem, it is offered the IbM program entitled ‘IbM Dongki: the Solution of Clean Water Supplying for the Hilly Area. The installation of the hydram pump is hoped to be able to solve the people problem for their difficulty to supply clean water. The machine is suitable to apply because it can flow the water from the springs into the people settlement located about 1 km above it. Besides, it is so economic, it does not need fuel or electricity. It uses only water falls power from the water flow of the springs. The maintenance of the machine is simple also.